2014
DOI: 10.3340/jkns.2014.56.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Non-Dural-Based Spinal Meningioma : The First Case Report of a Fibrous Subtype and a Review of the Literature

Abstract: Spinal meningiomas typically adhere to the dura matter. Non-dural based spinal meningiomas are rare and most are clear cell meningiomas. We report here the first case of a fibrous meningioma with non-dural attachment. The patient was a 49-year-old female, who complained of numbness in the legs and a gait disturbance. Magnetic resonance imaging revealed a 1.7×1.4-cm mass in the C7-T1 intra-dural extramedullary space, showing peripheral gadolinium enhancement without a "dural tail sign". A complete microsurgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In summary, this 66-year-old female presented with a spinal schwannoma with atypical imaging. Though the radiographic appearance of spinal schwannomas, demonstrating T2 hyperintensity with avid contrast enhancement has been well-described, 5,8 this patient's tumor was T2 hypointense and had a somewhat serpiginous morphology, leading the clinical team to believe this most likely represented an intradural vascular lesion. In fact, in the cervical region, T2 hypointensity has been used to differentiate the normal ganglia of the cervical sympathetic chain from schwannomas.…”
Section: Discussionmentioning
confidence: 89%
“…In summary, this 66-year-old female presented with a spinal schwannoma with atypical imaging. Though the radiographic appearance of spinal schwannomas, demonstrating T2 hyperintensity with avid contrast enhancement has been well-described, 5,8 this patient's tumor was T2 hypointense and had a somewhat serpiginous morphology, leading the clinical team to believe this most likely represented an intradural vascular lesion. In fact, in the cervical region, T2 hypointensity has been used to differentiate the normal ganglia of the cervical sympathetic chain from schwannomas.…”
Section: Discussionmentioning
confidence: 89%
“…3,5,6,[10][11][12][13][14][16][17][18]25,29,30) In such cases, the tumor is often attached to the nerve root. Lee et al reported that 15 (83.3%) of 18 cases of spinal meningiomas did not have a dural attachment, 34) and lack of dural attachment is characteristic of this disease. A case of deep sylvian meningioma without dural attachment is also reported recently.…”
Section: Fig 1 Lumbar Spine Ct Showed High Absorption At the L3 Vertebral Level (A) And Lumbar Mri T1-weighted Images Showed Faint High Smentioning
confidence: 98%
“…15,22,37) It also demonstrates a high absorption zone on CT. 23) Dural tail sign is not seen, in contrast to other meningiomas. 34,38) When a spinal cord tumor with these meningioma features is found, especially in young patients, the possibility of CCM should be kept in mind. 6,15) CCMs have greater recurrences compared with other meningiomas and is a WHO classification Grade II.…”
Section: Fig 1 Lumbar Spine Ct Showed High Absorption At the L3 Vertebral Level (A) And Lumbar Mri T1-weighted Images Showed Faint High Smentioning
confidence: 99%
See 2 more Smart Citations